Role of Eosinophils in Intestinal Inflammation and Fibrosis in Inflammatory Bowel Disease: An Overlooked Villain? - Jacobs, Inge; Ceulemans, Matthias; Wauters, Lucas; Breynaert, Christine; Vermeire, Séverine; Verstockt, Bram; Vanuytsel, Tim (Frontiers in Immunology, 2021)
Eosinophils are leukocytes which reside in the gastrointestinal tract under homeostatic conditions, except for the esophagus which is normally devoid of eosinophils. Research on eosinophils has primarily focused on anti-helminth responses and type 2 immune disorders. In contrast, the search for a role of eosinophils in chronic intestinal inflammation and fibrosis has been limited. With a shift in research focus from adaptive to innate immunity and the fact that the eosinophilic granules are filled with inflammatory mediators, eosinophils are becoming a point of interest in inflammatory bowel diseases. In the current review we summarize eosinophil characteristics and recruitment as well as the current knowledge on presence, inflammatory and pro-fibrotic functions of eosinophils in IBD and other chronic inflammatory conditions, and we identify research gaps which should be covered in the future.